Persilangan Budaya dan Hibriditas Dalam Film Mowgli:legend of the jungle (2018) - Nanda Sekar Rahayu (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
This study aims to analyze the representation of cultural intersection and the construction of hybrid identity in Mowgli: Legend of the Jungle (2018), directed by Andy Serkis, as a cultural text within the framework of the sociology of literature. This research employs a qualitative descriptive method, combining a sociological approach to literature with the theory of cultural hybridity. The theoretical framework is grounded in the works of Wellek and Warren, Ian Watt, Lucien Goldmann, and Georg Lukács, as well as Homi K. Bhabha’s concepts of hybridity and the third space. The data consist of dialogues, scenes, and visual symbols, which are analyzed interpretatively to examine the relationship between culture, power, and identity. The findings reveal that the film not only represents a binary opposition between Eastern and Western cultures but also demonstrates a process of cultural negotiation that produces a third space as a locus for the formation of hybrid identity. The character of Mowgli is portrayed as an ambivalent subject who integrates collectivist and rational values, reflecting identity dynamics in a postcolonial context. Furthermore, the film reflects hegemonic power relations while simultaneously presenting forms of resistance through local values emphasizing ecological harmony. The study concludes that cultural hybridity is a dynamic process involving negotiation and reinterpretation rather than a passive mixture. In the context of globalization, these findings highlight that cultural identity is fluid and continuously shaped through intercultural interactions, emphasizing the importance of adaptive strategies in sustaining local cultural identity.